1988
DOI: 10.1002/ajmg.1320310206
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental components of serum creatine kinase (CK) and pyruvate kinase (PK) in normal twins: Implication for genetic risks estimates in Duchenne muscular dystrophy carriers

Abstract: The serum activity of creatine kinase (CK) and pyruvate kinase (PK) was measured in 98 pairs of same-sex Brazilian twins. The purpose of this study was to estimate the genetic and environmental components of serum activity levels for both enzymes. Heritabilities were estimated separately by path analysis in each sex. The results showed that CK and PK activities are under genetic control in normal males and females. Environmental components were not statistically significant for CK or PK. The genetic component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Similarly, there is evidence indicating that genes affect plasma CK activity at rest. For example, hyperCKemia is reported to exist in some minor familial asymptomatic myopathies [12,22], and several twin studies have reported heritability estimates for CK activity, ranging from 16 % [4], to over 60 % [20,31,33,44]. There have also been instances of individuals demonstrating consistent plasma CK activities following eccentric exercise bouts of both the left and right arms [26,28].…”
Section: Abstract Genetics • Monozygous • Muscle Injury • Force Defimentioning
confidence: 99%
“…Similarly, there is evidence indicating that genes affect plasma CK activity at rest. For example, hyperCKemia is reported to exist in some minor familial asymptomatic myopathies [12,22], and several twin studies have reported heritability estimates for CK activity, ranging from 16 % [4], to over 60 % [20,31,33,44]. There have also been instances of individuals demonstrating consistent plasma CK activities following eccentric exercise bouts of both the left and right arms [26,28].…”
Section: Abstract Genetics • Monozygous • Muscle Injury • Force Defimentioning
confidence: 99%
“…The highest estimated hcritabilities were also observed among females unlikely to be heterozygotes for the abnormal gene (ta ble 3). The most likely explanation for such findings is that in these groups the majority of females arc probably noncarri ers of the defective gene, and therefore their serum enzyme levels follow the multifactorial pattern of inheritance observed for normal individuals [34][35][36], Probably the same effect would be expected among obligate carriers (mothers and daughters) with normal enzymes, but the sample is not large enough to test such hypothesis.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, investigations in normal individuals have also shown a sta tistically significant intrafamilial correla tion for both serum CK and PK [34][35][36], Estimates of the heritability of serum CK and PK in normal individuals suggest a multifactorial inheritance. In a study of normal female twins, Whitfield and Mar tin [34] estimated a heritability of 0.81 for CK, while Rapaport et al [36], in a large sample of monozygotic and dizygotic twins of both sexes, estimated a heritability of 0.55 for CK, 0.66 for PK and 0.49 for CK in female twins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects of this study were 338 previously re ported normal female controls with no family history of neuromuscular disease [Passos et al, 1985;Rocha, 1986;Rapaport et al, in press], 294 daughters of DMD obligate carriers and 124 obligate carriers whose data have been partially reported by Zatz et al (1976Zatz et al ( , 1978. A female was considered an obligate carrier when she had at least 2 affected sons or 1 son and another maternal affected male relative.…”
Section: Subjectsmentioning
confidence: 99%